STUDY INFORMATION PESTS, DURIAN IN DISEASE AND MITIGATION PROGRAM WITH VISUAL BASIC APPLICATIONS - Dapit Dapit; Ire Puspa Wardhani, SKom, MMSi (Jurnal Sistem Informasi, 2005)
Durian is one of the Indonesian native fruit. Many people are familiar with the durian.Durian with the peculiarities of form, taste and smell of this fruit causes many peopleliked.However, naming duria bark quite difficult for the novice investor, this is because thedurian growers need to know how the signs of pests and diseases and to overcomethem quickly and appropriately.This application is made for ease in detecting pests and diseases in durian, thisapplication is one of the development of artificial intelligence. In addition to detectionof pests and diseases in durian, this application also provides solutions to problemsarising durian crop.This application is created using Visual Basic 5.0 programming language, with theintention that the resulting view is User-Interface.